A Rare Cause of Dyspepsia: A Case Report of Gastric Diverticulum - Kow, Ren Yi; Ismail, Dhauiddin Hai; Md Saad, Khatrulnada; Japar Khan, Ed Simor Khan Mor (IIUM Medical Journal Malaysia, 2019)
A gastric diverticulum is an outpouching from the gastric mucosa. It is extremely rare. It is normally asymptomatic, but some may present with non-specific abdominal pain. A combination of upper gastrointestinal endoscopy and radiological contrast study such as oral barium study and computed tomography are needed to make a definite diagnosis and to rule out other associated pathology. Although treatment with medical therapy has been reported to be effective, the use of open and laparoscopic resection also yields a good outcome in the management of complicated gastric diverticulum. We present a case of symptomatic gastric diverticulum which has been successfully treated with medical therapy.